Efektivitas Pemerintah dalam Mencegah Serta Mengurangi Anak Jalanan di Kota Batam - Edo Clarita Samad; Tantimin Tantimin (Wajah Hukum, 2022)
The purpose of this study is to determine the negative impact that occurs due to urbanization or the large number of migrants entering the city of Batam from various regions without having expertise. This will cause various social problems. The Batam city government has prepared a regional regulation for handling the poor and neglected children. By using Non Doctrinal Sociological Research Methods, which means using empirical data obtained through interviews and observations, this study aims to examine the regulation of street children, social effectiveness, and the efforts made by the Batam City government in overcoming the problems of street children. The results of the study explain that the effectiveness of local regulations is still lacking and even the Batam city government has not done anything about the substance of the problems of street children.